International Financial Statistics Yearbook, 2003. - International Monetary Fund. Statistics Dept. (Washington, D.C. : International Monetary Fund, 2003)
The International Financial Statistics Yearbook, usually published in September, contains available annual data covering 12 years for countries appearing in the monthly issues of IFS. The IFS service is the standard source of international financial statistics. Additional time series in country tables and some additional tables of area and world aggregates are included in the Yearbook.
Off-Campus Access: No User ID or Password Required
On-Campus Access: No User ID or Password Required
Mode of access: Internet
Keywords: General Financial Markets; Investment Decisions; Portfolio Choice